THE SHRINES ECONOMY: A CASE STUDY OF RELIGIOUS TOURISM IN PAKISTAN - Zafar Ali (Journal of Religion and Society, 2025)
This research explores the economic and cultural significance of religious tourism in Pakistan, particularly focusing on the role of shrines as key destinations for both spiritual and cultural engagement. Pakistan is home to nearly 5,000 shrines that attract millions of pilgrims and tourists annually, contributing significantly to local economies. Shrines, revered by both Sunni and Shia communities, are not just places of religious importance but also centers of vibrant cultural activities. These sacred sites play a pivotal role in community cohesion, social mobilization, and cultural preservation. The study also highlights the evolution of shrines in Pakistan from spiritual centers to economic assets, emphasizing their dual role in fostering both spiritual well-being and economic development. Religious tourism, including the visitation of shrines, has a profound economic impact, stimulating local economies through tourism-related activities such as accommodation, transport, food services, and artisan crafts. However, challenges like inadequate infrastructure, political instability, and commercialization threaten the sustainability of these religious tourism sites. The research proposes strategies for enhancing the infrastructure and marketing of religious tourism, ensuring its long-term viability while preserving the sanctity of these sacred spaces. The findings underscore the potential of religious tourism to reduce poverty and stimulate economic growth, particularly in underdeveloped areas, while also promoting interfaith harmony and cultural understanding. Keywords: Religious Tourism, Shrines, Economic Impact, Sufism, Pakistan, Cultural Heritage, Pilgrimage, Infrastructure Development, Tourism Economy